Physicochemical and antioxidant properties of Bangladeshi honeys stored for more than one year - Islam Asiful; Khalil Ibrahim; Islam Nazmul; Moniruzzaman Mohammed; Mottalib Abdul; Sulaiman Siti; Gan Siew (BMC, 2012)
Abstract Background There is no available information on physicochemical and antioxidant properties on Bangladeshi honey. We investigated five different monofloral and three different multifloral honey samples collected from different parts of Bangladesh. Methods The levels of phenolics, flavonoids, ascorbic acid, ascorbic acid equivalent antioxidant content (AEAC), proline, protein and antioxidants were determined in the honey samples using ferric reducing antioxidant power (FRAP) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) assays. Results The highest level of phenolic was 688.5 ± 5.9 mg Gallic acid/kg, and the highest level of flavonoid was 155 ± 6.9 mg Catechin/kg. The highest color intensity was 2034.00 ± 17.5 mAU, and the highest protein content was 8.6 ± 0.0mg/g. High levels of proline (2932.8 ± 3.7 mg/kg), ascorbic acid (154.3 ± 0.3 mg/kg), AEAC (34.1 ± 1.4mg/100 g) and FRAP (772.4 ± 2.5 μmol Fe (II)/100 g) were detected in some of the samples, especially the multifloral honey samples, indicating good antioxidant properties. A strong positive correlation was found between phenolics, flavonoids, DPPH, FRAP and color intensity, indicating that in addition to total phenolic and flavonoid concentrations, color intensity and amino acid are good indicators of the antioxidant potential of honey. Except for a single sample (BDH-6), the honey samples stored for 1.5 years at room temperature still had 5-hydroxymethylfurfural (HMF) values within the recommended range (mean = 10.93 mg/kg), indicating that the rate of HMF production in Bangladeshi honey samples is low. Conclusion It is postulated that the low rate of HMF formation could be attributed to the acidic and low moisture content in the samples. In general, multifloral honeys have higher antioxidant properties based on their high levels of phenolics, flavonoids, AEAC, DPPH and FRAP when compared to monofloral honeys. We also found that monofloral honey samples from Guizotia abyssinica and Nigella sativa had high antioxidant properties.